Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

Evaluate [tex]\(\left(-3 g^2\right)^0\)[/tex] where [tex]\(g=0\)[/tex].

A. 3
B. -3
C. 1
D. The value is undefined.


Sagot :

First, we need to evaluate the expression [tex]\(\left(-3 g^2\right)^0\)[/tex] where [tex]\(g = 0\)[/tex].

1. Substitute [tex]\(g = 0\)[/tex] into the given expression:
[tex]\[ (-3 g^2)^0 \][/tex]

2. Calculate [tex]\(g^2\)[/tex] where [tex]\(g = 0\)[/tex]:
[tex]\[ g^2 = 0^2 = 0 \][/tex]

3. Substitute [tex]\(g^2 = 0\)[/tex] back into the expression:
[tex]\[ (-3 \cdot 0)^0 \][/tex]

4. Perform the multiplication inside the parentheses:
[tex]\[ -3 \cdot 0 = 0 \][/tex]

5. Now the expression simplifies to:
[tex]\[ 0^0 \][/tex]

6. According to mathematical conventions, the expression [tex]\(0^0\)[/tex] is typically defined as 1, though it can be debated in different contexts. However, in this case, we follow the standard convention:
[tex]\[ 0^0 = 1 \][/tex]

So, the value of the expression [tex]\(\left(-3 g^2\right)^0\)[/tex] where [tex]\(g = 0\)[/tex] is [tex]\(1\)[/tex].